Factors influencing maladaptive behaviour among street children in Khartoum, Sudan / Najla Abdallah Mohammed Ahmed - Najla Abdallah , Mohammed Ahmed (2020)
Children living on the streets are a common sight in Khartoum, the capital of Sudan, and in other parts of the country. In the case of Khartoum's street children, they have left their homes for the streets to satisfy their basic needs among which are food, alternate shelter and clothing. The absence of these things may force children to take to the streets where they think they have better opportunities to have access to their basic needs. These children are vulnerable and defenceless, may be pressed or intimidated into being involved in criminal activities, including in the illegal drug industry. While some street children earn their livelihood by cleaning cars and shining shoes, others get themselves involved in unlawful deeds such as pickpocketing, stealing and peddling drugs. This form of earning livelihood puts street children in extremely compromising conditions, jeopardising their health and social-psychological welfare by exposing them to risks of contracting infections and hostile treatment by law enforcement agencies. To address the issue of street children, this study aims to first, investigate the factors that determine maladaptive behaviour among street children. Second, this study intends to examine the coping strategies for the survival of the street children; and third, to analyse the effect of the length of stay on the street children’s behaviour. A total of 12 marketplaces in Khartoum state and its three municipalities, namely, Khartoum, Omdurman, North Khartoum (Bahri) were selected in the current study as these localities have massive numbers of street children, who seek job opportunities. Using a division by geographical clusters of the areas, 330 street children were selected as the sample of the study using a purposive sampling technique. Then, a quantitative survey was used to obtain data from the respondents. In addition, convenient sampling was used to gather 10 participants for a focus group discussion in each locality, Khartoum, Omdurman and North Khartoum. The obtained quantitative data were analysed through covariance-based Structural Equation Modelling using AMOS version 24. The qualitative data from the focus group discussions were organised and subsequently coded based on themes described by the respondents or others that were related to their responses. The results of the study revealed that there is a strong association among socio-economic status (SES), family factors, socio-psychological factors and maladaptive behaviour outcomes. SES and family factors increased the hardship and created harmful living conditions for the children on the street besides other negative social behaviours on the street that influenced their behaviour. Additionally, the ignorance in the street environment, the danger children face on the street, the interaction with people and peers do more harm than good to the street children even though the majority of these children are still staying with their families. The findings indicated that there is a significant association between the duration of stay on the street and maladaptive. In addition, the results of the qualitative analysis revealed the street peers were seen as the children’s biggest support system where they learn survival and secure job opportunities. Besides, the analysis of the qualitative data showed that some members of the public behave kindly towards the street children, while the quantitative data showed that peer and the public influenced their behaviour negatively. To cope with their hardship, street children were found to take substances such as drugs and alcohol and perform illegal activities in the streets. The key message delivered by this study is the government must make a clear policy to support poor families by distributing direct transfers (cash handouts) and the basic minimum income should be also secured to guarantee the children's welfare, security and sense of family life. A free education policy and fee waivers for all children below 18 years of age should be made compulsory. Moreover, free meals for poor children should also be warranted.